2019
DOI: 10.1007/s00540-019-02712-7
|View full text |Cite
|
Sign up to set email alerts
|

Placement of TOF-Cuff® on the lower leg for neuromuscular and blood pressure monitoring during anesthetic induction for shoulder surgeries

Abstract: Purpose The aim of this study was to compare two devices for neuromuscular monitoring during anesthetic induction. TOF-Cuff® was installed on the lower leg stimulating the tibial nerve, while the more conventional TOF-Scan® was installed over the ulnar nerve at the wrist. Methods Twenty adult patients were enrolled in this prospective, controlled study. Train-of-four (TOF) was recorded every 15 s until TOF ratio of 0%. Mean arterial blood pressure (MAP) was assessed with TOF-Cuff® and with standard anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…However, this study found a high failure rate for TOF-Cuff measurements on the lower limb. 27 In contrast, another 2020 study comparing TOF-Cuff and TOF-Scan found that the cuff recorded endpoints earlier than TOF-Scan. The authors of the study stated that, despite these differences, the results obtained with these methods may be important in clinical settings.…”
Section: Main Sectionsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, this study found a high failure rate for TOF-Cuff measurements on the lower limb. 27 In contrast, another 2020 study comparing TOF-Cuff and TOF-Scan found that the cuff recorded endpoints earlier than TOF-Scan. The authors of the study stated that, despite these differences, the results obtained with these methods may be important in clinical settings.…”
Section: Main Sectionsmentioning
confidence: 94%
“…It has built-in electrodes that stimulate the peripheral nerves located on the arm (most often the ulnar or median nerves), it is also possible to make measurements on the lower limb. 27 , 28 This monitoring system has been validated with mechanomyography, and the detected reaction is a change in cuff pressure generated by muscle contraction in response to a given stimulus. The great advantage of this device is the ability to make measurements at any patient position and the fact it has an autopilot mode, which detects changes in the patient’s position and automatically starts measuring vital functions.…”
Section: Main Sectionsmentioning
confidence: 99%
“…The sample size was chosen in accordance with our previous investigation concerning TS [8] and other similar studies [9,[11][12][13][14][15]. We already compared the TS and the TOF Watch accelerometer [8]; in this study, 32 patients were included and a mean bias of 26 s was observed between the two types of accelerometers.…”
Section: Methodsmentioning
confidence: 99%
“…This device does not require specific limb position or expensive components used with other monitoring systems. It is also able to be used for the lower leg, although the failure rate for a TOF measurement is higher than that measured by conventional acceleromyograph (TOF-Scan ® , IDMED, Marseille, France) in the upper arm [14]. Kameyama et al [15] reported that there were no differences in the onset of rocuronium-induced neuromuscular block, time to recovery of the first PTC twitch, time to recovery of the first twitch with TOF stimulation, and time to adequate reversal with sugammadex between TOF-Cuff ® and TOF-Watch ® .…”
Section: Measurement Of Neuromuscular Blockadementioning
confidence: 99%